2006
DOI: 10.1200/jco.2006.24.18_suppl.6089
|View full text |Cite
|
Sign up to set email alerts
|

Cost of febrile neutropenia management in cancer patients in Spain

Abstract: 6089 Background: Febrile neutropenia (FN), a dose-limiting event for many myelosuppressive chemotherapy (CT) regimens, often causes subsequent CT dose delays (DD) and reductions (DR), lengthens hospital stay and increases monitoring, diagnostic and treatment costs. No studies are known to date on economic costs of FN in common clinical practice in Spain. Methods: This is a multicentre, retrospective, observational chart review of adult patients with breast cancer, lung cancer or non-Hodgkin’s lymphoma (NHL) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…An analysis in >40,000 US patients found that, on average, an FN episode resulted in a median hospital stay of 6 days and a median cost of $8,376, with 35% of patients being hospitalised for at least 10 days [ 3 ]. Smaller studies from various western European countries have provided estimates of the average charge for FN-related hospitalisation ranging from €2,619 in Spain to €4,931 in France [ 4 , 104 , 105 ]. These findings highlight the need to implement official guidelines for preventing FN.…”
Section: Clinical Implications Of New Datamentioning
confidence: 99%
“…An analysis in >40,000 US patients found that, on average, an FN episode resulted in a median hospital stay of 6 days and a median cost of $8,376, with 35% of patients being hospitalised for at least 10 days [ 3 ]. Smaller studies from various western European countries have provided estimates of the average charge for FN-related hospitalisation ranging from €2,619 in Spain to €4,931 in France [ 4 , 104 , 105 ]. These findings highlight the need to implement official guidelines for preventing FN.…”
Section: Clinical Implications Of New Datamentioning
confidence: 99%
“…In the European study by Pettengell et al (2006), about 30% of patients with lymphoma received an RDI p85% of what was planned, and multivariate regression analysis showed that the occurrence of FN in the first cycle was a predictor of low RDI. A retrospective chart review carried out in 16 Spanish hospitals in 2005 found that of 83 patients with breast cancer who developed FN, 42% required one or more chemotherapy dose reductions, 31% required one or more chemotherapy dose delays, and 17% discontinued chemotherapy altogether (Mayordomo et al, 2006). Another subgroup analysis of this study was in 67 patients with lymphoma who developed FN.…”
Section: Why Should Nurses Care About Cin and Fn?mentioning
confidence: 80%
“…determined that the average total cost per episode was 4514 for patients with lymphoma (López et al, 2006) and 3519 for patients with breast cancer (Mayordomo et al, 2006). The median length of hospital stay was 8 days for patients with lymphoma and 6 days for patients with breast cancer, and, as in the early UK study, the main drivers of the cost of managing FN were hospitalisation and antibiotic treatment (López et al, 2006;Mayordomo et al, 2006).…”
Section: Why Should Nurses Care About Cin and Fn?mentioning
confidence: 96%
See 1 more Smart Citation
“…In a retrospective study from Spain, the estimated cost of FN was €3519 (∼£2360) per episode ( Mayordomo et al , 2006 ). This is broadly in line with estimates from the United Kingdom, where the reference cost (essentially the charge to the payer) for an admission with FN is approximately £3300–£4300 and a recent review conducted by the National Institute for Health and Clinical Excellence (NICE) estimated a cost of about £3330 per FN episode ( NICE, 2008 ).…”
Section: The Costs Of Fn: Direct and Indirectmentioning
confidence: 99%